Urgensi Keluarga dalam Pendidikan Karakter - imam catur pratomo; Yusuf Tri Herlambang (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2021)
Decreasing attitudes and character of children today such as promiscuity, inappropriate clothing styles, and loss of manners. The current condition of the nation's children is like losing their identity, therefore we need a character education in education. Character education is important in education. The purpose of character education is to shape and create human beings who have good morals, traits, behavior and character. If a nation has citizens with good character and quality, that nation will become a great nation and also be respected by other nations. This character education must also be supported by several parties including schools, the community and most importantly the family. Because the family is the first guide, teacher, and example for their children and also has the biggest role in this character education. Therefore, the family must provide a reflection of good attitudes, behavior and character towards children.